PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi di Dinas Kebersihan dan Pertamanan Kota Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is a study that tested the effect of transformational leadership and work motivation on employee performance with job satisfaction as a mediating variable in the Dinas Kebersihan dan Pertamanan Kota Semarang. This research has been tested on respondents who worked in the Dinas Kebersihan dan Pertamanan Kota Semarang as employees, using SPSS Statistics Test. The results of this study explain transformsional leadership, work motivation influence on employee performance, transformational leadership, work motivation and job satisfaction influence on employee performance. Job satisfaction can not mediate transformational leadership and work motivation on employee performance because the value of the mediating coefficient is smaller than direct influence both on transformational leadership and work motivation on employee performance.   Keywords: transformational leadership, work motivation, job satisfaction, employee performance